2011
DOI: 10.1002/jsfa.4311
|View full text |Cite
|
Sign up to set email alerts
|

The effects of moderately oxidised dietary oil with or without vitamin E supplementation on performance, nutrient digestibility, some blood traits, lipid peroxidation and antioxidant defence of male broilers

Abstract: The results showed that a milder oxidative stress occurred by supplementation of moderately oxidised oil to the diet of broilers and vitamin E supplementation had been helpful in alleviating lipid peroxidation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
15
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 58 publications
3
15
0
Order By: Relevance
“…According to Kanner (2007) and Hamilton and Kirstein (2008) this result could be related with the pre-stabilisation of fat with antioxidant before diet manufacture, and an adequate level of fat soluble vitamins and minerals from the raw materials and the vitamin/mineral mixture (which provides 20 and 60 ppm of α-tocopherol and Zn, respectively) included in the diets. However, while some works have reported a reduction in negative effects of highly-oxidised diets on animal performance when antioxidants were supplemented (Lin et al, 1989;Bitam et al, 2004), most works in the literature did not record any positive effect on growth performance from their additional supplementation (Schiavone et al, 2010;Açikgöz et al, 2011). These results reveal that when the usual stabilisation of oil and vitamin and mineral supplementation to meet animal requirements takes place, the additional inclusion of α-tocopherol and Zn seems to be unnecessary to ensure an adequate performance.…”
Section: Resultsmentioning
confidence: 79%
“…According to Kanner (2007) and Hamilton and Kirstein (2008) this result could be related with the pre-stabilisation of fat with antioxidant before diet manufacture, and an adequate level of fat soluble vitamins and minerals from the raw materials and the vitamin/mineral mixture (which provides 20 and 60 ppm of α-tocopherol and Zn, respectively) included in the diets. However, while some works have reported a reduction in negative effects of highly-oxidised diets on animal performance when antioxidants were supplemented (Lin et al, 1989;Bitam et al, 2004), most works in the literature did not record any positive effect on growth performance from their additional supplementation (Schiavone et al, 2010;Açikgöz et al, 2011). These results reveal that when the usual stabilisation of oil and vitamin and mineral supplementation to meet animal requirements takes place, the additional inclusion of α-tocopherol and Zn seems to be unnecessary to ensure an adequate performance.…”
Section: Resultsmentioning
confidence: 79%
“…() and Açlkgöz et al . () reported that oxidized oil did not affect the protein digestibility in rats or in broilers, respectively. However, in the current study, dry matter, protein and energy ADC were observed with increasing dietary oxidized oil inclusion.…”
Section: Discussionmentioning
confidence: 96%
“…The basic structural difference between them is the number of double bonds of the side chain. This results in a change in biological activity of vitamin E. In general, α-tocopherol is considered as a standard of comparison for determining the activity of other forms of vitamin E (Açıkgöz et al, 2011). Vitamin E can be found in natural or synthetic form, and is present in vegetable oils, egg, liver, and some vegetables and in general in green leaves.…”
Section: Vitamin In the Feed For Broilers And Ways Of Supplymentioning
confidence: 99%